From Bat Mitzvah to the Bar: Religious Habitus, Self-Concept, and Women's Educational Outcomes. Issue 2 (April 2022) - Horwitz, Ilana M.; Matheny, Kaylee T.; Laryea, Krystal; Schnabel, Landon
This study considers the role of religious habitus and self-concept in educational stratification. We follow 3, 238 adolescents for 13 years by linking the National Study of Youth and Religion to the National Student Clearinghouse. Survey data reveal that girls with a Jewish upbringing have two distinct postsecondary patterns compared to girls with a non-Jewish upbringing, even after controlling for social origins: (1) they are 23 percentage points more likely to graduate college, and (2) they graduate from much more selective colleges. We then analyze 107 interviews with 33 girls from comparable social origins interviewed repeatedly between adolescence and emerging adulthood. Girls raised by Jewish parents articulate a self-concept marked by ambitious career goals and an eagerness to have new experiences. For these girls, elite higher education and graduate school are central to attaining self-concept congruence. In contrast, girls raised by non-Jewish parents tend to prioritize motherhood and have humbler employment aims. For them, graduating from college, regardless of its prestige, is sufficient for self-concept congruence. We conclude that religious subculture is a key factor in educational stratification, and divergent paths to self-concept congruence can help explain why educational outcomes vary by religion in gendered ways.